(untitled) (Global Journal of Human-Social Science, 2020)
This study aimed to know the current status of existing multimedia materials in the multimedia language labs in departments and institution of Aligarh Muslim University. A survey questionnaire was applied to collect data and analysed by using SPSS software version-17. Moreover, questionnaire was only distributed among the students and teachers group who are using multimedia materials for learning English language and teachers who are teaching them in the Multimedia lab with the integration of technology. The study was led during the session 2016-2017 academic years. This paper is one the chapters of Ph.D thesis submitted for award of the degree of doctor of philosophy.